lncRNA KCNQ1OT1 reverses the effect of sevoflurane on hepatocellular carcinoma progression via regulating the miR-29a-3p/CBX3 axis - Zhou,Weifu (2021)
Sevoflurane (SEVO) is widely applied as an anesthetic, which exerts antitumor capacity in various cancers, including hepatocellular carcinoma (HCC). Previous studies indicated that long non-coding RNA KCNQ1 opposite strand/antisense transcript 1 (KCNQ1OT1) was upregulated, while microRNA-29a-3p (miR-29a-3p) was downregulated in HCC. Thus, we aimed to explore the roles of KCNQ1OT1 and miR-29a-3p in HCC cells exposed to SEVO. Cell proliferation, apoptosis, migration, and invasion were assessed by the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay, flow cytometry, and transwell assays, respectively. The levels of genes were determined by quantitative real-time polymerase chain reaction (qRT-PCR) or western blot. Furthermore, the interaction between miR-29a-3p and KCNQ1OT1 or chromebox protein homolog 3 (CBX3) was predicted by Starbase or Targetscan, and then confirmed by dual-luciferase reporter assay. We found that the levels of KCNQ1OT1 and CBX3 were decreased, while miR-29a-3p was increased in SEVO-treated HCC cells. KCNQ1OT1 overexpression weakened the inhibitory effects of SEVO on HCC cell proliferation, apoptosis, migration, and invasion. Interestingly, KCNQ1OT1 bound to miR-29a-3p, and miR-29a-3p targeted CBX3. KCNQ1OT1 upregulated CBX3 level by repressing miR-29a-3p expression. Furthermore, KCNQ1OT1 exerted tumor promotion in HCC cells via suppressing miR-29a-3p to regulate CBX3 expression. Collectively, our findings demonstrated that KCNQ1OT1 regulated the antitumor effects of SEVO on HCC cells through modulating the miR-29a-3p/CBX3 axis, providing a theoretical basis for the treatment of HCC.